Status of Amphibian Habitats and their Conservation in Agricultural Fields of Sindh, Pakistan - Dhani Bux Mashori,; Kalsoom Shaikh,; Memon, Quratulain; Ali Raza Soomro,; Shaukat Ibrahim Abro, (Dialogue Social Science Review (DSSR), 2025)
ABSTRACT: Suitable environmental conditions are necessary for stable survival of amphibians as they have transparent skin that remains susceptible to dreadful pollutants which may affect their development and survival and may also make them vulnerable to mortality. In this context, we proposed to explore the agricultural fields in one of the main provinces of Pakistan “Sindh” to record the status of amphibian’s habitats as well as their diverse forms. Field surveys were conducted and water quality of habitats was analyzed through parameters: electric conductivity (EC), total dissolved solids (TDS), total hardness (T. Hard), total alkalinity (T. Alk), sulphate (SO4) and phosphate (PO4) using equipment of analytical grade. The agricultural fields were recorded to embrace species: H. tigerinus, E. cyanophlyctis, A. hazarensis and B. Stomaticus. The value of water quality parameters was recorded as extremely high as permissible limit of environmental protection agency. Water quality changes were prominent every month and values of parameters remained higher during spawning, hatching and metamorphosing. Such water quality of habitats especially during breeding season may deteriorate amphibian populations at large; therefore, conservation efforts may be taken to save amphibians from possible decline in future. Keywords—Amphibian fauna, Ecology, Water quality, Physico-chemical parameters.